The Hole - Hubley, John; Hubley, Faith (Lightyear, 1993)
The Hole (1962): Dizzy Gillespie provides an improvised voiceover as two construction workers in a hole in the ground argue about the nature and possibility of accidents, which leads them into a discussion about nuclear disarmament and the possibility of nuclear war. [www.bcdb.com]